Improving Reading Comprehension Ability with the Think Pair Share Cooperative Learning Model and Library Utilization of Writing Skills Courses in the Department of Indonesian Language and Literature Semester II at FKIP UMSU Academic Year 2021-2022 - Amnur Rifai Dewirsyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Writing skills courses in higher education are learning that requires students to be able to understand reading both in text and context. Students need to be given the opportunity to understand the reading so that they can pour what is on their mind into written form. Ability to read comprehension with the implementation of the Think Pair Share (TPS) Cooperative Learning Model and Library Utilization. Reading Comprehension Ability in Basic Competence of Writing Skills from the results of observations. Cycle I showed the average percentage score of Reading Comprehension in Basic Competence of Writing Skills of 76.19%, the score then increased in cycle II to 84.57% in cycle II. There was an increase in the average percentage score of Reading Comprehension in Basic Competence of Writing Skills from cycle I to cycle II of 8.38%. The results of the average percentage of Reading Comprehension Ability in the Basic Competence of Writing Skills also shows that more than 75% of the indicators of success in Reading Comprehension Basic Competence in Writing Skills have been achieved.